METHODOLOGY FOR CREATING SCRIPTED "LESSON CATALOGS" FOR CHEMISTRY TEACHERS (Proceedings of Scientific Conference on Multidisciplinary Studies, 2023)
In this article, the method of creating scripted "lesson catalogs" for chemistry teachers is given, which can be used by young teachers, future chemistry teachers to organize chemistry lessons, how to organize chemistry lessons, how to achieve an effective result, suggestions and recommendations about what methods, methods and tools should be used to achieve the intended goal from the lesson. Also, to increase students' interest in chemistry, real-life examples, interesting stories from the life path of chemist scientists, information on the connection of chemistry with other subjects through interdisciplinary integration, PISA studies and methods of using STEAM education in chemistry classes are presented.